Makna Frasa Berturut-Turut dalam Pasal 19 Ayat (3) Undang-Undang Jabatan Notaris - Ni Made Dwita Andayana Dewi; I Wayan Novy Purwanto (Fakultas Hukum, Universitas Warmadewa, 2025)
The clarity of meaning in every provision of the law is essential to prevent differences in interpretation that may hinder the realization of legal certainty and justice in its aplication. This research intends to evaluate the juridical implications of successive Notarial instrument executed outside from the notary's residence with regard to their legality and to interpret the phrases